Ancient Christian commentary on Scripture ; NT v.VI - Bray, Gerald Lewis (Downers Grove, IL IVP, 1998)
Contents : v. VI : Romans. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Romans -- commentaries; Bible. N.T. Romans -- criticism, interpretation, etc. -- History, early church, ca. 30-600 -- sources